Crystallinity as a tunable switch of poly(L-lactide) shape memory effects. (February 2017) - Sobota, Michał; Jurczyk, Sebastian; Kwiecień, Michał; Smola-Dmochowska, Anna; Musioł, Marta; Domański, Marian; Janeczek, Henryk; Kawalec, Michał; Kurcok, Piotr
Abstract: Materials with shape memory effect (SME) have already been widely used in the medical field. The interesting part of this group is represented by double function materials. The bioresorption and SME ability are common in polyesters implants. The first information about vascular stent made of bioresorbable polyester with SME was published in 2000. However, there are not many investigations about SME control of elements in the aspect of material processing. In the present work, the ability to control the shape memory (SM) of bioresorbable and semicrystalline poly( L -lactide) (PLLA) is investigated. The studies are based on the unexpected effect of material orientation which was demonstrated even at low percentage deformation in crystallized mould injected material. The presented studies revealed that the different degrees of crystallinity obtained during processing might be a useful switch to create a tailored SME for a specific application. The prepared samples of variable morphology revealed a possibility to control the value of material stress during permanent shape recovery. The degree of shape recovery of the prepared samples was also controlable. The highest stress value observed during permanent shape recovery reached 10 MPa for the sample annealed 60 min at 115 °C even when the sample was only deformed in 8%. The other significant aspect of this work is to present the problem of slow crystallization of the material during and after processing (cooling rate) as well as the possibility of negative SME change during the shelf life of the fabric. Graphical abstract: